2016
DOI: 10.1302/0301-620x.98b8.37117
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of the anterior cruciate ligament and its relevance to the technique of reconstruction

Abstract: Anterior cruciate ligament (ACL) reconstruction is commonly performed and has been for many years. Despite this, the technical details related to ACL anatomy, such as tunnel placement, are still a topic for debate. In this paper, we introduce the flat ribbon concept of the anatomy of the ACL, and its relevance to clinical practice. Cite this article: Bone Joint J 2016;98-B:1020-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
70
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 46 publications
1
70
0
1
Order By: Relevance
“…42 Following an extensive research on the anatomy of ACL in recent years, some researchers have introduced a flat ribbon concept of ACL anatomy and its relevance to the surgical technique of ACL reconstruction. 6,21 Oshima et al 43 found that the cross-sectional shape of the four-fold semitendinosus tendon graft was oval and proved the superiority of SBO technique over SBR technique. Nowadays, femoral oval The Journal of Knee Surgery tunnel technique has been gradually accepted in clinical practice and achieved a satisfactory function of the knee.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…42 Following an extensive research on the anatomy of ACL in recent years, some researchers have introduced a flat ribbon concept of ACL anatomy and its relevance to the surgical technique of ACL reconstruction. 6,21 Oshima et al 43 found that the cross-sectional shape of the four-fold semitendinosus tendon graft was oval and proved the superiority of SBO technique over SBR technique. Nowadays, femoral oval The Journal of Knee Surgery tunnel technique has been gradually accepted in clinical practice and achieved a satisfactory function of the knee.…”
Section: Discussionmentioning
confidence: 99%
“…39 The anatomic landmarks for the ACL reconstruction have been investigated in recent years, proper placement of the graft was a critical factor for the ACL reconstruction, and anatomical reconstruction of the ACL was widely accepted. 6,10 Recently more studies have found that the traditional SB ACL reconstruction could neither restore full rotational stability nor biomechanical properties of the knee and researchers have been exploring ways to improve the surgi-cal technique. 22,40 The DB ACL reconstruction could effectively restore the rotational stability of the knee and reduce the forward instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stability of the knee joint is achieved by cooperation of static and dynamic stabilisers such as ligaments and muscles. There is disagreement among orthopaedic society about the number, location or structure of knee ligaments with new concepts being developed [13,14] and old verified. It is widely accepted that the knee joint is one of the most complex joints of the human body.…”
Section: Anatomy and Biomechanics Of Knee Jointmentioning
confidence: 99%
“…been investigated and the findings have resulted in modifications in the techniques of reconstruction following rupture. 4 The injury is usually due to a pivoting movement, which provokes both the ligament rupture and shear forces across the articular surface, with cartilage and menisci lesions often associated with acute ACL ruptures. 5 The goals of ACL reconstruction are the restoration of normal knee anatomy and function, reestablishment of biological and biomechanical homeostasis, and prevention of osteoarthritis (OA).…”
mentioning
confidence: 99%